2021
DOI: 10.1186/s12885-021-07816-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles shed from gastric cancer mediate protumor macrophage differentiation

Abstract: Background Peritoneal dissemination often develops in gastric cancer. Tumor-associated macrophages (TAMs) are present in the peritoneal cavity of gastric cancer patients with peritoneal dissemination, facilitating tumor progression. However, the mechanism by which macrophages differentiate into tumor-associated macrophages in the peritoneal cavity is not well understood. In this study, the interplay between gastric cancer-derived extracellular vesicles (EVs) and macrophages was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…Numerous studies have shown the ability of tEVs to polarize TAMs towards pro-tumorigenic MHC-II-phenotypes. 6366 In this respect, our data suggest that tEVs CSC may be the main tEV subset responsible for the reported TAMs polarization.…”
Section: Discussionmentioning
confidence: 61%
“…Numerous studies have shown the ability of tEVs to polarize TAMs towards pro-tumorigenic MHC-II-phenotypes. 6366 In this respect, our data suggest that tEVs CSC may be the main tEV subset responsible for the reported TAMs polarization.…”
Section: Discussionmentioning
confidence: 61%
“…In the study, patients with PM showed an increased number of TAM and M2 macrophages, upregulated levels of angiogenesis in the peritoneum and macrophages, and increased levels of epidermal growth factor and vascular endothelial growth factor-expressing macrophages. Although the mechanical aspect of TAM as a potential therapeutic target is still not well understood, previous studies have shown that M2-like macrophage infiltration is highly associated with PD-L1 expression in GC cells, and that extracellular vesicles derived from GC play a role by affecting macrophage phenotypes [ 97 , 98 ]. Considering these results, immunotherapy or cancer vaccines targeting TAM may be a promising strategy for PM treatment.…”
Section: Potential Rationale Of Immunotherapy In Pm Of Gcmentioning
confidence: 99%
“…These EVs stimulate the motility, invasiveness, and stemness of colorectal cancer cell lines. Cancer cells communicate with the microenvironment for progression through EVs [ 61 , 162 , 163 , 164 ]. MiR-370-3p-containing EVs from breast cancer cells induce IL-6, IL-8, and IL-1β secretion by suppressing the cylindromatosis-/NF-κB-signaling pathway in fibroblasts [ 58 ].…”
Section: Metastasismentioning
confidence: 99%